The Social Reality of Health on Premarital Sexual Behavior among Adolescents in Makassar - Hanifah, Astin Nur; Lubis, Halimatussakdiyah; Harfika, Meiana; Zulham, Zulham; Sambo, Sri Wahyuni; Surtikanti, Surtikanti (International Journal of Health Sciences, 2024)
During adolescence, significant physical and sexual changes occur so that sexual attraction to the opposite sex is quite large and sexual drive also develops. The results of the Indonesian Population and Family Planning Program survey in 2013 showed that more than 60% of teenagers in Indonesia had had premarital sex. Around 53% of women aged 10-19 years had sexual relations during adolescence, while the number of men who had sexual relations was more than double that of women. The aim of this research is to determine the correlation between teenagers' knowledge of unmarried sexual behavior in Makassar State High Schools. The research methodology used in this research is an observational analytical design with a cross sectional research design with a sample size of around 79 respondents. The sampling technique used in this research is simple random sampling. The data collection instrument used in this research was a questionnaire. The conclusion is that data analysis uses the Chi Square test. The statistical test results obtained a significance value of 0.004 (p <0.05), so it can be concluded that Ho is rejected (there is a significant relationship between teenagers' knowledge of unmarried sexual behavior in Makassar State High School.